(untitled) (Research, Society and Development, 2021)
Considering that the valuation of rural land is still a subject that has been little studied and explored, mainly in the State of Amazonas, due to the lack of literature and specialized professionals, this study aimed to apply valuation methodologies in rural land located in the Project of Rural Settlement for Agrarian Reform Iporá, Manápolis branch, municipality of Rio Preto da Eva, Amazonas. Efforts to carry out this research consisted in the search for a definition of parameters for the valuation of properties in rural areas of Amazonas. The research was permeated by the concepts of engineering evaluations and as a field research strategy the case study was chosen according to Yin (2015), based on the quali-quantitative evidence observed. The method of analysis selected was the Direct Comparison of Market Data, in which the value of the land or its improvements is obtained by comparing market data relating to other land with similar characteristics, using specific factors according to reality area or region, by technical treatment of its attributes. In the universe of existing lands in the Manápolis branch, one land was chosen evaluating (main) and nine (nine) samples similar to the evaluated sample element. All sample elements were homogenized using factors so that the sampling error was minimized. At the end of this research, we concluded that factors such as location, land regularity, easy access, drainage routes in a practical situation, among others, influence the valuation of rural land in Amazonas municipalities.